Meningkatkan Kesadaran Orang Tua dan Anak Melalui Penyuluhan Mengenai Penerapan Protokoler Kesehatan di masa Pandemi Covid – 19 di Paud Nur Qolbu Lingkungan Perumnas Ciracas Kelurahan Ciracas Kecamatan Serang Kota Serang - Marthalena; Siska Mardiana; Rethorika Berthanilla (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
Maintaining cleanliness and environmental health from an early age is one of the most important factors that must be considered in everyday life, especially now that our country and even the world is experiencing a covid-19 pandemic, therefore personal and environmental health needs to be considered, especially for children. children and elderly parents. The problems faced by service partners, which lie in the lack of knowledge about maintaining cleanliness during the covid-19 pandemic, and the lack of supporting facilities such as: hand sanitizers, masks, etc. The purpose of holding this service activity is to increase knowledge to the community about the importance of clean living. The implementation method carried out in this activity is through the socialization stage, the preparation stage and the evaluation stage. The result is an increased understanding in the community about the importance of keeping the environment clean, by always washing hands after leaving the house, maintaining distance, not littering, and always wearing masks when doing activities outside the home.